Pickering Emulsion and Derived Materials - Syuji Fujii (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Particle-stabilized emulsions, today often referred to as Pickering/Ramsden emulsions, are vital in many fields, including personal care products, foods, pharmaceuticals, and oil recovery. The exploitation of these Pickering emulsions for the manufacture of new functional materials has also recently become the subject of intense investigation. While much progress has been made over the past decade, Pickering emulsion still remains a rich topic since many aspects of their behavior have yet to be investigated. The present "Pickering Emulsion and Derived Materials" Special Issue aims to bring together research and review papers pertaining to the recent developments in the design, fabrication, and application of Pickering emulsions. The themes include, but are not limited to: 1. Interactions of colloidal particles confined at fluid interfaces 2. Pickering emulsion-based polymerization 3. Interfacial assembly and emulsion stabilization 4. Rheology of particle laden interfaces and Pickering emulsions 5. Functional materials templated from Pickering emulsions